Karakterisasi Morfologi Bunga dan Buah Abnormal Kelapa Sawit (Elaeis guineensis Jacq) Hasil Kultur Jaringan - Helen Hetharie; Gustav A. Wattimena; Maggy Thenawidjaya S.; Hajrial Aswidinnoor; Nurita Toruan-Mathius; Gale Ginting (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2007)
Tissue culture-derived plants of oil palm (Elaeis guineensis Jacq) can produce abnormal female dan male flowers, especially female, which develop into mantled fruit. This abnormality have caused yield lost up to 40%. The objectives of this research were to study the stages of flower development in which the abnormality started to appear, to characterize the morphology of the abnormal flower and fruit, and to determine the degree of abnormality. Plant materials used in this research were MK152, MK 176, MK 203, MK163, MK104, MK 212 and MK 209 clones obtained from the collection of "Badan Pengkajian dan Penerapan Teknologi (BPPT)" in Ciampea, Bogor. Characterization of abnormality at the flowering stage was conducted  based on morphological performance at several stages of flower development, while the degree of abnormality at fruiting stage was determined based on the condition of carpel, mesocarp and seed. Normal flower and fruit of the same clone were used as the control. The results showed that the abnormality started at primordial stage of flower organ formation. Supplement carpel was found surrounding gynoecium for the abnormal female flower, which was composed of three to six carpels present at  separate whorl of flower. Abnormal male  flower had no additional whorl of  flower, instead stamens were converted into carpel-like structures. In this case, number of carpels structure depends on the degree of abnormality. There were three levels of abnormality, i.e. light abnormality (AbR), heavy abnormality (AbB) and severe abnormality (AbSB). The severe abnormal fruit was seedless, with soft mesocarp (AbSB1) and woody mesocarp (AbSB2).   Key words : oil palm, mantled fruit, supplement carpel, flower whorl, tissue culture